Assessment of glycogen phosphorylase isoenzyme BB as a biomarker for pre-eclampsia and small for gestational age. (26th February 2015) - McCarthy, Fergus; Doyle, Aisling; Khashan, Ali; Kenny, Louise
Abstract: Background: Glycogen phosphorylase is a key enzyme in the regulation of glycogen metabolism and consists of three isoenzymes, including glycogen phosphorylase isoenzyme BB (GPBB). Pre-eclampsia, gestational hypertension, and small-for-gestational-age (SGA) infants are complications in about 15% of all nulliparous pregnancies. Biomarkers for these adverse pregnancy outcomes remain elusive. GPBB has been proposed as a potential biomarker for the detection of these adverse outcomes. We aimed to investigate this hypothesis. Methods: Blood samples from women with pre-eclampsia or SGA were analysed from the time of disease presentation and from samples collected at 15 and 20 weeks' gestation. They were compared with control samples obtained from women recruited to the Screening for Pregnancy Endpoints (SCOPE) study. These control samples were from healthy women with uncomplicated pregnancies matched for age, ethnicity, parity, body-mass index, and gestational age. GPBB concentrations were measured with ELISA (Diacordon, Diagenics, Essen, Germany). Findings: Significant differences in GPBB were observed between all three gestations (p=0·03). GPBB concentrations were higher in women with pre-eclampsia than in controls at the time of disease presentation (term pre-eclampsia n=14, median 22·2 ng/mL [IQR 15·1–39·8] vs 16·9 [10·4–19·1], p=0·04; preterm pre-eclampsia n=11, 23·1 [11·2–30·9] vs 17·2 [9·8–19·1], p=0·04) and at 20 weeks' gestation (n=39, 23·0 [15·6–31·4] vs 17·0 [13·4–23·6]; p=0·04). GPBB concentrations were also significantly higher in women with SGA than in controls at the time of disease detection (n=23, 22·7 [12·6–25·5] vs 17·0 [9·8–18·0]; p=0·03) but significantly less than in controls at 15 weeks' gestation before disease detection (n=25, 16·0 [12·1–23·2] vs 22·2 [17·0–28·9]; p=0·02). Interpretation: We have shown that significant variation of GPBB concentrations occurs in normal pregnancy, pre-eclampsia, and SGA pregnancies. GPBB in healthy pregnancy lowers as pregnancy progresses from the first to the third trimester. GPBB might, therefore, be useful as a biomarker in early pregnancy and at the time of disease in the prediction of both preterm and term pre-eclampsia and SGA. Funding: National Institute for Health Research, SCOPE Study was funded by the Health Research Board. This work was performed in the Irish Centre for Fetal and Neonatal Translational Research and partly supported by Science Foundation Ireland.